Household Accessibility and Residential Relocation in Older Adults. (5th December 2018) - Granbom, Marianne; Perrin, Nancy; Szanton, Sarah; K.M. Cudjoe, Thomas; Gitlin, Laura N
Abstract: Objectives: It is unclear how home environmental factors influence relocation decisions. We examined whether indoor accessibility, entrance accessibility, bathroom safety features, housing type, and housing condition were associated with relocations either within the community or to residential care facilities. Methods: We used prospective data over 4 years from the nationally representative National Health and Aging Trends Study in the United States of Medicare beneficiaries 65 years and older living in the community (N = 7, 197). We used multinomial regression analysis with survey weights. Results: Over the 4 years, 8.2% of the population moved within the community, and 3.9% moved to residential care facilities. After adjusting for demographics and health factors, poor indoor accessibility was found to be associated with moves within the community but not to residential care facilities. No additional home environmental factors were associated with relocation. Discussion: One-floor dwellings, access to a lift, or having a kitchen, bedroom, and bathroom on the same floor may help older adults age in place. Understanding which modifiable home environmental factors trigger late-life relocation, and to where, has practical implications for developing policies and programs to help older adults age in their place of choice.